Analysis of Customer Intention in Home Ownership Credit Products (KPR) Using Murabahah Contracts at BSI KCP Ciputat - Muhammad Faiq Abdullah Syafie (Islamic Marketing Review, 2023)
The aim of this research is to analyze the influence of Sharia KPR characteristics, price levels and financing procedures on customer interest in Home Ownership Credit (KPR) products at Bank Syariah Indonesia (BSI) KCP Ciputat. This research method uses a quantitative approach by conducting a survey of 120 active customers of Bank Syariah Indonesia (BSI) KCP Ciputat. This research uses structural equation analysis (SEM-PLS) to evaluate the relationship between constructs. Next, the data was processed using SMARTPLS 4 software. The results or findings based on the results of the analysis that have been carried out can be concluded that there are two significant variables, namely 1) the price level variable 2) the financing procedure variable. These two variables have a significant effect on interest. On the other hand, the characteristics of Sharia KPR do not have a significant effect on customer interest in KPR products using murabahah contracts at Bank Syariah Indonesia (BSI) KCP Ciputat.